FIELD PROPERTIES AND SETTLEMENT CALCULATION OF SOIL-CEMENT COLUMN IMPROVED SOFT SUBSOIL - A CASE STUDY - J. C. Chai; S. Y. Liu; Y. J. Du (Lowland Technology International, 2002)
The unconfined compression strength, standard penetration test (SPT) results for soil-cement columns and the field loading tests results of the composite subsoil at Lian-Yun-Gang section, Xu - Lian expressway, China, were presented. The Methods for calculating the settlement of the soil-cement column improved soft subsoil were discussed. It is recommended that the stiffness of the "slab" on the top of the improved subsoil should be flexible "slab". the equilibrium method for the improved layer and the average stress method for the underlying unimproved soft layer are prefered, while in the case of a stiff "slab", the average modulus method for the improved layer and the combined method for the underlying unimproved layer are prefered. Finally, the settlements of the soil-cement column improved subsoil at Lian-Yun-Gang section were evaluated by the suggested methods and compared with the field data. The stress concentration ratio (n) is back-calculated, and it showed that n value increased with the increased of the area replacement ratio.